2022
DOI: 10.3390/curroncol29090489
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Virtual Cancer Care on Chemotherapy Delivery and Clinical Outcomes in Colorectal Cancer Patients Receiving Systemic Therapy: A Pre- and Intra-Pandemic Analysis

Abstract: (1) Background: The coronavirus 2019 pandemic has resulted in an abrupt transition to virtual oncology care worldwide. This study’s objective is to evaluate chemotherapy delivery and clinical outcomes in patients on systemic treatment for colorectal cancer before and during the pandemic. (2) Methods: Clinical data was collected on patients with colorectal cancer receiving intravenous chemotherapy at The Ottawa Hospital from June 2019 to March 2021. Patients were stratified by whether they were started on chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The authors found no differences in rates of serious side effects, hospital admissions, or mortality between groups . Similar studies demonstrated that safety, efficiency, and outcomes were preserved during the COVID-19 era among patients treated with systemic therapy managed via telemedicine . To our knowledge, this study represents the first investigation of the safety of remote care among a cohort of patients treated with radiotherapy.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The authors found no differences in rates of serious side effects, hospital admissions, or mortality between groups . Similar studies demonstrated that safety, efficiency, and outcomes were preserved during the COVID-19 era among patients treated with systemic therapy managed via telemedicine . To our knowledge, this study represents the first investigation of the safety of remote care among a cohort of patients treated with radiotherapy.…”
Section: Discussionsupporting
confidence: 52%
“…35 Similar studies demonstrated that safety, efficiency, and outcomes were preserved during the COVID-19 era among patients treated with systemic therapy managed via telemedicine. 36,37 To our knowledge, this study represents the first investigation of the safety of remote care among a cohort of patients treated with radiotherapy. Although the rate of safety events per patient (ie, 765 total events, 0.27 events per patient per year) seems high, it reflects the culture of safety within our department and highlights the widespread adoption and ease of use of our patient safety reporting system.…”
Section: Discussionmentioning
confidence: 98%
“…Most patients with unresectable advanced disease can initiate first-line SSA therapy and avoid more intensive treatments such as chemotherapy, targeted agents or PRRT until progression [13,14]. Although virtual care has been shown to be safe in patients undergoing active treatment and even combination intravenous chemotherapies, its role is felt to be greatest in patients with a stable clinical status [15][16][17]. GEP-NETs may be well suited for virtual care under this principle.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual care provides flexibility to patients and can reduce the time away from work, family and other commitments. It also seems to be safe, even in patients undergoing active treatment for cancer, although high-quality data are lacking [16]. From a system standpoint, virtual care is efficient and cost-effective [7,22].…”
Section: Discussionmentioning
confidence: 99%